Failure maps and optimal design of metallic sandwich panels with truss cores subjected to thermal loading. (September 2016) - Yuan, Wu; Song, Hongwei; Huang, Chenguang
Abstract: Sandwich panels with truss cores have been widely investigated due to their superior mechanical performances. When being used in the thermal protection system of a high-speed aircraft, sandwich panels are usually subjected to intense thermal loading and may fail due to various mechanisms. This paper presents a theoretical and numerical analysis on the failure mechanisms and optimal design of metallic sandwich panels with truss cores subjected to uniform thermal loading. Five failure modes are considered: global buckling, face sheet buckling, face sheet yielding, core member buckling and core member yielding. Failure maps of sandwich panels with several truss core topologies are developed based on these failure modes. Taking the five failure modes as constraint conditions, sandwich panels with truss cores are optimally designed for the minimum weight at given thermal loadings. It is found from the optimal analysis that sandwich panels with Kagome and X-type truss cores are more efficient than those with tetrahedral and pyramidal truss cores. Sandwich panels with fully-clamped boundary conditions have superior thermal loading resistance than those with simply-supported boundary conditions. Highlights: Critical loads of five possible failure modes of SPTCs are derived. Failure maps versus thermal loading obtained for various core configurations. Optimal result obtained by numerical model instead of confluence of constraints. Minimum weight and optimal geometric parameters of SPTCs are obtained.